Risk assessment of tire wear in the environment - a literature review - Müller, Kathrin; Unice, Kenny; Panko, Julie; Ferrari, Benoît J D; Breider, Florian; Wagner, Stephan (Environmental science--processes & impacts, 2025)
Tread wear emission inventories, uncertainty about the future development of the emissions and observed adverse effects of tire constituents in the environment have raised the need for an environmental risk assessment of tire wear emissions. While progress has been made in exposure and hazard assessment of tire wear emissions in the environment, the complexity of tire wear emissions creates some challenges which are not yet overcome. For instance, there is no universal agreed risk assessment framework for tire wear emissions. It was proposed that existing frameworks, for example for microplastics, be adapted to tire wear emissions because there are similarities between particulate tire wear emissions and microplastics, particulate material with a polymer backbone. The review discusses whether these are applicable for tire wear emissions and proposes adaptations. It provides a comprehensive assessment of exposure and hazard data for tire wear emission and reveals needs and data gaps for environmental risk assessment of tire wear. Based on the available exposure and hazard data sets a low risk prioritization of particulate tire wear emissions in aquatic and terrestrial environments was estimated. Risk prioritization of leachables from tire emissions is not yet possible due to inconsistent hazard data sets. It was found that for environmental risk assessment, insufficient consistent exposure and hazard data is available. It is suggested to develop clear harmonization guidelines how exposure and hazard studies should be designed. Such guidelines should be developed between all relevant stakeholders covering the entire product life cycle.